THE PREVALENCE OF EIMERIA AND CRYPTOSPORIDIUM IN CATTLE IN AL-DIWANIYAH AND AL-NAJAF PROVINCES - MAYTHAM ASKAR ALWAN AL-SHABBANI (The Bioscan, 2025)
This study is to isolate and diagnose some intestinal protozoa, namely Eimeria and Cryptosporidium, that cause diarrhea in cattle. To this end, the study investigates the frequency of infection in different districts and localities in Al-Diwaniyah and Al-Najaf Provinces. Also, the study examines whether age and sex are effective factors in the prevalence of that disease in animals. The results of the laboratory and microscopical examination of feces revealed that while 41 (out of 160) animals were infected with Eimeria spp., that is 25.62 %, these animals tested negative for Cryptosporidium spp. Additionally, the infection was higher in both the young animals (47.36 %) and in cows (26.82 %). The highest rates of infection with Eimeria spp. have been detected in Al-Diwaniyah province (33.33 %) and the lowest rates have been detected in the zoological field of the Faculty of Veterinary Medicine, University of Kufa (14.28 %). In terms of age, statistically significant differences (p< 0.05) in infection frequencies have been found. Non-significant differences in infection frequencies have been found between sex on the one hand and the geographical region on the other hand (p>0.05). Conclusions: The infections with coccidia were found in all the studied regions. As for age, they were common in young and older animals but most frequent in young animals. Also, both male and female animals were vulnerable to infection with coccidia.